2016
DOI: 10.1128/jcm.01655-16
|View full text |Cite
|
Sign up to set email alerts
|

Application of Mass Spectrometry Technology to Early Diagnosis of Invasive Fungal Infections

Abstract: We recently developed a mass spectrometry (MS) procedure based on the detection of a serum disaccharide (MS-DS) in patients with invasive candidiasis (IC). Invasive candidiasis (IC) and invasive aspergillosis (IA) are major life-threatening nosocomial invasive fungal infections (IFIs) (1-3). Although less prevalent, mucormycosis (MM) is an emerging problem. Progress in antifungal therapy has not significantly reduced the high rates of morbidity and mortality associated with IFIs, particularly in intensive care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 36 publications
0
30
1
Order By: Relevance
“…24 These differences have also been reported for other novel markers, such as serum disaccharide detected with mass spectrometry (MS-DS). 27 Although our study was not primarily designed for assessing the impact of BDG positivity on the prognosis of IA (and thus the analysis was not adjusted for other factors possibly influencing mortality), we observed lower 180-day survival in patients with IA and a positive vs negative BDG. More research with appropriate adjustment is warranted to confirm these findings and enrich our understanding on the possible prognostic role of BDG in patients with IA.…”
Section: As Shown Inmentioning
confidence: 74%
See 1 more Smart Citation
“…24 These differences have also been reported for other novel markers, such as serum disaccharide detected with mass spectrometry (MS-DS). 27 Although our study was not primarily designed for assessing the impact of BDG positivity on the prognosis of IA (and thus the analysis was not adjusted for other factors possibly influencing mortality), we observed lower 180-day survival in patients with IA and a positive vs negative BDG. More research with appropriate adjustment is warranted to confirm these findings and enrich our understanding on the possible prognostic role of BDG in patients with IA.…”
Section: As Shown Inmentioning
confidence: 74%
“…In this regard, Pazos and colleagues observed that BDG tends to become positive before GM in some patients with IA, probably reflecting the fact that the kinetics of blood release and clearance of different fungal markers is not the same during the course of infection . These differences have also been reported for other novel markers, such as serum disaccharide detected with mass spectrometry (MS‐DS) …”
Section: Discussionmentioning
confidence: 97%
“…Until this moment, none of the serological tests currently on the market were efficient for the diagnosis. Apparently MS-DS could fill this gap, improving the promptness of a clinical diagnosis of this high lethal condition 11 . In most cases, the infection is rapidly progressive with high risk of death, especially if underlying risk factors (i.e., metabolic acidosis) are not corrected in time 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, results of evaluation of this method suggest the possibility of panfungal analyses and diagnosis of IMI for which currently there are no available commercial serological tests that are efficient for the diagnosis. However, it has to be highlighted that this biological test requires further evaluation and validation in multicenter studies [134].…”
Section: Future Perspectivesmentioning
confidence: 99%